Automated text-level semantic markers of Alzheimer's disease - Sanz, Camila (2022)
INTRODUCTION: Automated speech analysis has emerged as a scalable, cost-effective tool to identify persons with Alzheimer?s disease (AD). Yet, most research is undermined by low interpretability and specificity. METHODS: Combining statistical and machine learning analyses of natural speech data, we aimed to discriminate AD dementia (ADD) patients from healthy controls (HCs) based on automated measures of domains typically affected in AD: semantic granularity (coarseness of concepts) and ongoing semantic variability (conceptual closeness of successive words). To test for specificity, we replicated the analyses on Parkinson?s disease (PD) patients. RESULTS: Relative to controls, ADD (but not PD) patients exhibited significant differences in both measures. Also, these features robustly classified between ADD patients and HCs (AUC = 0.8), yielding near-chance classification between PD patients and HCs (AUC = 0.65). DISCUSSION: Automated discourse-level semantic analyses can reveal objective, interpretable, and specific markers of ADD, bridging well-established neuropsychological targets with digital assessment tools.